Lipid composition and nutritional quality of some commercially available cold pressed oils - Dean, Lisa L. (Frontiers in Nutrition, 2025)
Consumer interest in alternatives to highly refined oils from soybean and corn for culinary applications has resulted in an increase in the availability of alternatives, especially cold pressed ones. Sources that were once only known to certain regions or cultures are now becoming more mainstream. In addition, the interest in sustainability in the agricultural sector has led to the usage of seeds from previous “waste” sources. The fatty acid profiles, phytosterols and tocopherols were evaluated in some cold pressed oils from small processors. These included benne (black sesame), okra seeds, peanuts, pecans, pumpkin seeds, and sunflower seeds. Polyunsaturated fatty acid contents ranged from 1.8% in sunflower oil to 44.3% in pumpkin seed oil. Cold pressed oils do not have the phytosterols and tocopherols removed by further refining. All the oils tested contained significant amounts of phytosterols with the lowest levels of Beta-sitosterol in the okra seed oil (29.0 mg/100 g) and the highest in the sunflower seed oil (251 mg/100 g). The tocopherols present in the oils were in agreement with literature reports for oil seeds and tree nuts with significant amounts of the alpha and gamma forms. Unusually, the benne oil was found to have large amounts of the Beta form (8.8 mg/g oil). Use of these oils can make positive contributions to human health by providing significant amounts of these lipid nutrients to the diet.